Clinical association and potential molecular mechanisms of neonatal sepsis and necrotizing enterocolitis - Liu, Xue; Sun, Wenqiang; Bian, Jingtao; Li, Yihui; Jin, Xinyun; Zhu, Xueping (Frontiers in Molecular Biosciences, 2025)
BackgroundNecrotizing enterocolitis (NEC) is a severe intestinal disease affecting premature infants, with mortality rates of 20%–30%. Clinical studies have shown that neonatal sepsis (NS) is an independent risk factor for NEC; however, the shared molecular mechanisms and diagnostic biomarkers between these two conditions remain poorly understood. This study aims to explore the shared molecular mechanisms underlying the association between NS and NEC and to identify potential diagnostic biomarkers.MethodsThis study combines clinical cohort analysis with transcriptomic analysis. First, we enrolled 74 NEC infants and 74 gestational age/birth weight-matched controls from Children’s Hospital of Soochow University and quantified the association between NS and NEC using logistic regression analysis. Second, we jointly analyzed transcriptome data from NS (GSE25504) and NEC (GSE46619) datasets to screen for overlapping differentially expressed genes (DEGs) and constructed a protein-protein interaction (PPI) network to identify hub genes. Subsequently, the diagnostic efficacy of core genes was evaluated using independent validation cohorts (GSE297483 and GSE69686). Finally, a transcription factor-mRNA regulatory network was constructed using the TRRUST database to explore the underlying regulatory mechanisms.ResultsClinical association analysis showed a significantly increased risk of NEC in NS infants (OR = 3.02, P = 0.002). Infants in the NEC group had significantly higher systemic inflammatory markers and a higher incidence of sepsis (60.81% vs. 33.78%) compared to the control group. Mechanistic studies identified 70 co-directional overlapping DEGs, with 69 upregulated and 1 downregulated. These genes were significantly enriched in neutrophil chemotaxis and IL-17 signaling pathways (P < 0.05). Further investigation identified FPR1, S100A12, and CSF3R as potential biomarkers involved in immune response and inflammatory processes. External validation showed moderate diagnostic performance, with areas under the curve (AUCs) ranging from 0.723 to 0.813. Transcriptional regulation analysis revealed that transcription factors including SPI1, NFKB1, and JUN were identified as potential regulators of inflammatory genes.ConclusionThis study suggests that neonatal sepsis may serve as a risk factor for NEC development through shared inflammatory pathways involving FPR1, S100A12, and CSF3R. These genes demonstrated diagnostic potential across both conditions and appear to mediate inflammatory processes involving immune cell recruitment. While these findings suggest new directions for early identification in high-risk infants, further clinical validation is necessary to confirm therapeutic implications.